ANALISIS PENGUASAAN KATA KERJA â€œQU BIEâ€ DAN â€œFEN BIEâ€ PADA MAHASISWA 2016 BAHASA MANDARIN UNTAN - Indrayani, Stevi; Thamrin, Lily; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractVerbs are one of the most commonly used syntax in Chinese expression and important materials in Chinese teaching. For example, verbs "qubie" and "fenbie" are often used in daily spoken Chinese. There are some differences in the usage of these two words, which makes students incorrect on using them. In order to understand the situation and difficulties of Tanjungpura University FKIP Untan Chinese Education Program batch 2016 students in mastering the verbs "qubie" and "fenbie", the author uses the test method to test the students. The test results show that some of the usages of these two modal words have been mastered well, but some of them are not mastered very well. The correct rates of "Qu Bie" and "Fen Bie" are 53.47% and 65.08% respectively.Keywords: Allegation, Difference and Distinguish, Mastery Analysis?Verb